TINGKAT BAHAYA EROSI PADA KAWASAN HUTAN PRODUKSI WILAYAH GEROKGAK, KABUPATEN BULELENG, BALI - -, WIYANTI (Agrotrop : Journal on Agriculture Science, 2012)
Erosion Hazard on Production Forest Area at Gerokgak, Buleleng, Bali The experiment about erosion hazard has been conducted at production forest area at Gerokgak, Buleleng, Bali. The aims of the research are to predict erosion and determine the erosion hazard. The method used in this research is USLE (Universal Soil Loss Equation). Land unit was classified base on slope, land use pattern, and soil type. The result of the research showed that soil erosion was classified as moderate to heavy. The moderate erosion was occurred at land unit 18 (58.104 tons/ha/year); heavy erosion at land unit 19 (65.059 tons/ha/year); 20 (31.342 tons/ha/year); and 24 (52.895 tons/ ha/year); and very heavy erosion at land unit 16 (934.799 tons/ha/year); 17 (668.072 tons/ha/year); 21 (266.799 tons/ha/year); 22 (285.735 tons/ha/year); 23 (65.652 tons/ha/year), 24 (260.962 tons/ ha/year); 25 (295.207 tons/ha/year); 26 (249.304 tons/ha/year and 271.329 tons/ha/year); and 27 (130.757 tons/ha/year).
Keywords: erosion hazard, production forest.